PENDETEKSI KEBOCORAN GAS LPG DENGAN SENSOR MQ-6 - MARDIANSYAH, ARI (Journal of Informatics and Computing, 2024)
With the large use of LPG gas as an important fuel in households. There are several dangers that often occur, one of which is LPG gas leaks. LPG gas has a very high level of risk as a cause of explosion compared to oil fuel. There have been many cases of LPG gas cylinder explosions that have occurred in Indonesia. For this reason, it is important to have a tool that can detect LPG gas leaks to prevent accidents. One of the sensors used is the M6 ​​sensor. This article reviews the literature on LPG gas leak detection tools using the MQ-6 sensor. The MQ-6 sensor can detect gas at a distance of 30 cm with a detection speed of around 0.16 seconds because this sensor is very sensitive to LPG gas.